2018
DOI: 10.1302/0301-620x.100b6.bjj-2017-1212.r1
|View full text |Cite
|
Sign up to set email alerts
|

En bloc resection of pelvic sarcomas with sacral invasion

Abstract: We propose a comprehensive classification of surgical approaches for tumours of the pelvis with sacral invasion. Analysis showed that this classification helped in the surgical management of such patients and had predictive value for surgical outcomes. Cite this article: Bone Joint J 2018;100-B:798-805.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
2
13
0
2
Order By: Relevance
“…However, the positive margin rate may potentially be further decreased if the proposed CSGS technique are used in conjunction with computer-assisted techniques, thereby improving both identification of planned osteotomy site and execution of bony cutting. The overall local recurrence in the current study was 20% among the range of literature reported recentl y[ 1 , 14 , 21 ]. One patient (no.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…However, the positive margin rate may potentially be further decreased if the proposed CSGS technique are used in conjunction with computer-assisted techniques, thereby improving both identification of planned osteotomy site and execution of bony cutting. The overall local recurrence in the current study was 20% among the range of literature reported recentl y[ 1 , 14 , 21 ]. One patient (no.…”
Section: Discussionsupporting
confidence: 49%
“…Resections were classified according to the Peking University classificatio n[ 1 ] of surgical approaches for pelvic tumors with sacral invasion (Fig. 1 ): Briefly, pelvisacral (Ps) I, II, and III resections refer to sagittal osteotomies through the ipsilateral wing of the sacrum, through the sacral midline, or lateral to the contralateral sacral foramina, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1978, Steel reported limb salvage procedure with internal pelvic resection and femoral head (FH) exclusion for the first time, and with the advances in imaging, surgery, anesthesiology, and prosthesis, limb salvage therapy was gradually being applied to the treatment of malignant pelvic bone tumors 1. However, the high rate of recurrence and complications has remained troubling 25. Apart from the surgeons’ technical level, a more important reason lies in the fact that surgeons need to build the tumor and its adjacent structures in the brain with each separate image, such as roentgenogram, computed tomography (CT) scan, and magnetic resonance imaging (MRI), which may result in inaccurate resection and reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…MRI images were mapped to CT images through affine and diffeomorphic registration algorithm, which were all implemented in open- 1D, E) and then exported to stereolithographic (STL) format and opened in a workstation running Reverse Engineering (RE) software Creo Parametric 2.0 (Parametric Technology Co., USA) to identify the characteristics for the resection margin and cut plane. In this study, the minimum tumor-free margin of 20 mm in bone were regarded as sufficient as indicated by a series of studies reporting the satisfactory tumor-free margin ranging from 5 to 15 mm and 20 mm for chondrosarcoma (21)(22)(23) and osteosarcoma with sensitive response to neoadjuvant chemotherapy (24). The cut plane was then designed with a minimum 20-mm margin to the tumor with comprehensive consideration of surgical approach, tumor-free requirement, avoidance of neurovascular injury and viscera organs, feasibility to the installation of the patient-specific instrument (PSI).…”
Section: Endoprosthesis Design With 3dmmi Techniquementioning
confidence: 99%